Developmental associations between joint engagement and autistic children's vocabulary: A cross-lagged panel analysis. (February 2021) - Bottema-Beutel, Kristen; Kim, So Yoon; Crowley, Shannon; Yoder, Paul J
Cross-lagged panel analysis was used to examine associations between two joint engagement variables; higher order supported joint engagement and higher order supported joint engagement that co-occurs with caregiver's follow-in talk (higher order supported joint engagement + follow-in), and expressive and receptive vocabulary in a group of young autistic children ( n  = 91) with language delay (mean chronological age = 39 months). Variables were measured twice, 8 months apart. Coefficients for cross-lagged variable pairs were derived from structural equation models. Early higher order supported joint engagement was significantly associated with later expressive and receptive vocabulary ( b s = 0.18 and 0.26, respectively), and early higher order supported joint engagement + follow-in was significantly associated with later expressive and receptive vocabulary ( b s = 0.14 and 0.15, respectively). Associations between early vocabulary and later joint engagement were not significant. Linear contrasts between cross-lagged associations did not show a significantly superior association for any early joint engagement variables and later vocabulary variables. However, our results suggest that higher order supported joint engagement and higher order supported joint engagement + follow-in may be useful initial intervention targets for developmental interventions aimed at promoting autistic children's language development who are initially language delayed. Lay abstract: In this study, we used a cross-lagged panel analysis to examine correlations over time between two types of engagement between children and their parents and children's later expressive and receptive vocabularies. This kind of design can help researchers understand which early developmental achievements "drive" later developmental achievements. It is important for intervention researchers to know which developmental achievements happen first, so that they can set intervention goals appropriately. The two joint engagement variables we examined were (a) higher order supported joint engagement, which occurs when caregivers influence their child's play with toys and the child reciprocally responds to the caregiver, but does not manage the interaction by shifting gaze between the toys and the caregiver, and (b) higher order supported joint engagement that co-occurs with caregiver's follow-in talk (higher order supported joint engagement + follow-in). Follow-in talk occurs when the caregiver talks about objects and events that the child is focused on. Ninety-one autistic children ( n  = 91) with language delay (mean chronological age = 39 months) participated, along with their primary caregivers. Each of the four variables was measured twice, 8 months apart. Our statistical procedures showed that early higher order supported joint engagement and early higher order supported joint engagement + follow-in were significantly associated with later expressive and receptive vocabulary. In contrast, associations between early vocabulary variables and later joint engagement variables were not significant. Our results suggest that higher order supported joint engagement and higher order supported joint engagement + follow-in may be useful initial intervention targets, for developmental interventions aimed at promoting language development in autistic children who are initially language delayed.